Book Review - Bentham’s Theory Of Fictions (UUM Journal of Legal Studies, 2015)
This review1 is a commentary on Ogden’s introduction to Jeremy Bentham’s Theory of Fictions. 2 It tries to show that legal fiction suggests fraud by the user, and more, may well mislead the court. Ogden’s introduction separates into five major headings. There is a still a tendency among practising lawyers to speak in pejorative tones about the study of jurisprudence. This tendency may be an indicium of a failure to understand the law’s underlying reasoning, and instead, to prefer the law’s cultus,3 manifesting as fraud and abuse of legislative power. In this view, the reasons are the rules themselves. Therefore, this review addresses Ogden’s sections on legal fictions,the vocabulary of fiction,the technique of definition, and fallacies. The review will not discuss Ogden’s conclusion or his note on Bentham’s method of composition.